Poverty, vulnerability, and child labour: evidence from Uganda - Angemi, Diego (2008)
Notwithstanding a decade of unprecedented social and economic reforms in Uganda, poverty, vulnerability, and child labour severely undermine the government's overarching goal of poverty eradication. This thesis unfolds by disclosing unprecedented insight on the relationship between vulnerability and poverty, the merits of quantitative vis-a-vis qualitative approaches to poverty analysis, and the role of child labour in Uganda. Chapter I generates the first ever appraisal of vulnerability in Uganda. The findings support the hypothesis that during the past decade, alongside sharp reductions in poverty, vulnerability to poverty in Uganda declined from 57% in 1992/93 to 25% in 1999/00. Such results highlight the importance for policy makers to distinguish between the effective implementation of poverty-prevention and poverty-reduction programmes. Chapter II deepens our understanding of poverty in Uganda, by integrating the country's qualitative and quantitative data, enriching information from one approach with that from the other, and merging the findings from these two approaches into one set of policy recommendations. The results show that this dual approach to poverty analysis enriches the discussion of poverty trends by drawing attention to aspects of poverty and wellbeing neglected by simple construction of poverty indicators. Since poverty of the household is an important determinant of agricultural child labour (ILO, 1992), chapter III investigates the extent to which children contribute to the household's agricultural activities. The conclusion that children play an important role in the farming activities of Ugandan agricultural households is supported by two key findings: (i) Child labour accounts for approximately 9% of the household's annual agricultural earnings; and (ii) on the bases that most child labour is performed on the family farm and smoothly functioning labour markets are rare, land ownership increases the household's demand for child labour in agricultural activities.